The Fight against Corruption in Indonesia = Der Kampf gegen Korruption in Indonesien - Schütte, Sofie Arjon (2007)
Progress in the fight against corruption in Indonesia is slow and faces many obstacles and countervailing forces. Since the fall of Soeharto, a number of new Laws establishing a more effective anticorruption legislative framework and institutions were put on the statute books. With the presidency of Soesilo Bambang Yudhoyono, the Executive has shown more commitment to the fight against corruption than under his predecessors. The Corruption Eradication Commission (KPK) and the special Anticorruption Court established in late 2003 and 2004 respectively are seen by many as the last resort in a judicial system infested with corruption. The KPK has a wide-ranging mandate in both the prevention and prosecution of corruption, and has secured public trust through the bringing of a number of high-profile cases to court and upholding its own institutional integrity. Due to a recent ruling by the Constitutional Court, however, the fate of the Special Anticorruption Court post-2009 is now in t